2015
DOI: 10.1111/apt.13271
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant GSTP1 promoter methylation predicts short‐term prognosis in acute‐on‐chronic hepatitis B liver failure

Abstract: SUMMARY BackgroundGlutathione-S-transferase P1 (GSTP1) methylation has been demonstrated to be associated with oxidative stress induced liver damage in acute-on-chronic hepatitis B liver failure (ACHBLF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…In CHB patients who progress to HCC, GST-P1 expression decreases compared to patients in earlier stages of the disease, and its level correlates positively with MDA and xanthine oxidase expression and negatively with GSH levels [326]. Specifically, acute-on-chronic hepatitis B patients are characterized by frequent GSTP1 (hyper)methylation, leading to the absence of expression of this protein [327]. GSTP1 (hyper)methylation is a hallmark of carcinogenesis and the most common molecular alteration in human cancer [328, 329].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…In CHB patients who progress to HCC, GST-P1 expression decreases compared to patients in earlier stages of the disease, and its level correlates positively with MDA and xanthine oxidase expression and negatively with GSH levels [326]. Specifically, acute-on-chronic hepatitis B patients are characterized by frequent GSTP1 (hyper)methylation, leading to the absence of expression of this protein [327]. GSTP1 (hyper)methylation is a hallmark of carcinogenesis and the most common molecular alteration in human cancer [328, 329].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…GSTP1 (hyper)methylation is a hallmark of carcinogenesis and the most common molecular alteration in human cancer [328, 329]. In HBV infection as well, high GSTP1 methylation status predicts a poor prognosis [327]. …”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Biochemical measurements were conducted as our previously described. 8 The serum biochemical markers (COBAS integra 800, Roche Diagnostics, Penzberg, Germany) included alanine aminotransferase, aspartate aminotransferase, gammaglutamyl transferase, fasting blood glucose (FBG), cholesterol, triglycerides (TG), high-density lipoprotein, and low-density lipoprotein, blood urea nitrogen, and creatinine. Hematological markers (Sysmex XE-2100; Sysmex Corporation, Chuoku, Kobe, Japan) included hemoglobin (HGB), white blood cells, and platelets.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has several limitations including poor patient compliance, deficient reproducibility, sampling error, and lack of dynamic surveillance and follow up. Liver biopsy leads to pain in 30% of the patients, severe complications in 0.3% of the patients, and death in 0.03% of the patients . Previous studies have demonstrated that ultrasonography allows for reliable and accurate detection of NAFLD, compared with histopathology .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation